Bending-moment-based approach to match damage-equivalent strains in fatigue testing. (1st January 2021) - Castro, Oscar; Berring, Peter; Branner, Kim; Hvejsel, Christian Frier; Yeniceli, Süleyman Cem; Belloni, Federico
Highlights: The effects of combined loads on the structural response at the material level in all points of a beam-like structure subjected to pure bending moments during multi-axial fatigue tests are considered. The proposed approach only requires, as inputs, the bending moments applied to the structure and the ratio between the cross-section stiffnesses. The manufacturers do not have to provide any confidential information that compromises the design of the structure. Abstract: A bending-moment-based approach that matches with damage-equivalent strains in fatigue testing of beam-like structures, such as wind turbine blades, is proposed in this study. A modified bending moment variable, which is proportional to longitudinal strains developed in beams when subjected to pure bending moments, is first defined. This variable is then used to develop the proposed fatigue approach, which considers the effect of combined loads on the response of the structure at the material level. The proposed approach only requires, as inputs, the bending moments applied to the structure and the ratio between the cross-section stiffnesses.